PERBEDAAN SUHU DAN WAKTU PENYIMPANAN SPESIMEN SPUTUM TERHADAP HASIL PEMERIKSAAN MIKROSKOPIS BAKTERI TAHAN ASAM - Alfi Agilia Saputri, Nianda; Ilmi Sufa , Hafizah; Kurniati, Iis; Dermawan, Asep (Jurnal Kesehatan Siliwangi, 2024)
Sputum specimens should ideally be examined immediately to ensure accurate BTA (Acid Resistant Bacteria) microscopic examination results. The limited number of ATLMs while the large amount of sputum causes delays in examination. The purpose of the study was to determine the differences in characteristics and the number of BTA based on the International Union Againtst Tuberculosis and Lung Disease (IUATLD) scale of sputum examined immediately with those stored at temperatures (23-27°C) and (35-39°C) with storage times of 6.5 and 7.5 hours. The research design used was quasi-experimental. The results showed there were changes in the characteristics of sputum stored at temperatures (23-27°C) and (35-39°C) with storage times of 6.5 and 7.5 hours against sputum examined immediately. Sputum examined immediately had a BTA count of 1+. Sputum stored at temperature (23-27°C) at storage times of 6.5 and 7.5 hours the number of BTA is 1+, while sputum stored at temperature (35-39°C) at storage times of 6.5 and 7.5 hours the number of BTA is 2+. So it can be concluded that there are changes in the characteristics of sputum stored at temperatures (23-27°C) and (35-39°C) with storage times of 6.5 and 7.5 hours. There is no difference in the number of BTA scale (IUATLD) of sputum stored at temperature (23-27°C) at storage times of 6.5 and 7.5 hours, while sputum stored at temperature (35-39°C) at storage times of 6.5 and 7.5 hours there is a difference in the number of BTA scale (IUATLD) of sputum specimens examined immediately.